ESG and KBV Integration for Sustainable Value Creation: A Systematic Literature Review - Rousilita Suhendah; Elsa Imelda; Ivan Kanel; Arifuddin Arifuddin; Asri Usman (Penerbit Goodwood, 2026)
Purpose: This study examines how Environmental, Social, and Governance (ESG) criteria integrate with the Knowledge-Based View (KBV) within strategic knowledge management to generate sustainable value and competitive advantage. Research Methodology: A Systematic Literature Review (SLR) was conducted using a structured PRISMA-based protocol to identify and select relevant scientific articles. The selected studies were analyzed using thematic and narrative approaches to explore conceptual developments, empirical findings and research gaps. Results: The findings reveal that ESG has evolved from a non-financial reporting mechanism to a strategic information system embedded in organizational knowledge processes. The results indicate diverse relationships between ESG practices and corporate performance, while highlighting key challenges, such as greenwashing, reporting inconsistencies, and limitations of global standards. ESG is a knowledge-intensive process that involves knowledge creation, retention, and dissemination. Conclusions: This study demonstrates that the KBV framework effectively explains ESG’s role of ESG in fostering sustainable value creation and long-term competitive advantage through strategic knowledge integration. Limitations: This study is limited to published academic literature included in the SLR process, which may exclude relevant gray literature or emerging industry practices and findings. Additionally, the findings depend on the scope and quality of the selected studies, which may affect generalizability. Contributions: This study integrates ESG and KBV into a unified analytical framework within strategic knowledge management. It advances theoretical understanding by positioning ESG as a knowledge-based strategic resource and provides direction for future research on sustainable value creation and organizational performance.